1996
DOI: 10.1139/v96-208
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of directed epoxidations of 22-hydroxy-Δ23-sterol side chains

Abstract: A series of 22-hydroxy-A''-sterols comprising (3~,5a,6~,22S)-6-methoxy-3,5-~y~l0-25,26,27-trinorcholest-23-en- 22-01 (6), (3~,5a,6~,22S,23E)-6-methoxy-3,5-cyclo-26,27-dinorcholest-23-en-22-ol (7), 3P,5a,6P,22R)-6-methoxy-23-methyl-3,5-cyclo-25,26,27-trinorcholest-23-en-22-ol(10), 3~,5a,6~,22S,23~-6-methoxy-3,5-cyclo-26,27-dinorcholest-23-en-22-01 ( l l ) , and 3~,5a,6~,22R)-6-methoxy-3,5-cyclo-26,27-dinorergost-23-en-22-ol (12) were subjected to epoxidation with /)I-chloroperbenzoic acid and [err-butyl hydrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several vanadyl complexes show excellent antibacterial activity against Streptococcus pneumoniae , wherein the vanadium complexes inhibit substrate transport through the cell membrane . Examples of catalytic applications by vanadyl complexes relevant to the present study are the use of VO(acac) 2 as a catalyst in the stereoselective epoxidation of 2,2-hydrox-δ-sterol side chains using MCPBA or tert -butyl hydroperoxide as oxidant, giving the erythro form as the major sterol enantiomer . Polymer-bound VO(acac) 2 is a catalyst for the conversion of benzene to phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Several vanadyl complexes show excellent antibacterial activity against Streptococcus pneumoniae , wherein the vanadium complexes inhibit substrate transport through the cell membrane . Examples of catalytic applications by vanadyl complexes relevant to the present study are the use of VO(acac) 2 as a catalyst in the stereoselective epoxidation of 2,2-hydrox-δ-sterol side chains using MCPBA or tert -butyl hydroperoxide as oxidant, giving the erythro form as the major sterol enantiomer . Polymer-bound VO(acac) 2 is a catalyst for the conversion of benzene to phenol.…”
Section: Introductionmentioning
confidence: 99%
“…201 Other synthetic studies on the construction of the sterol side chain which have been reported include the use of chlorosulfones, 202 methods for the formation of 26,27-cyclopropylsterols, 203 and the application of 22-cupriosteroids. 204 Stereoselectivity in the epoxidation 205 and hydroxylation 206 of side chain double bonds has been examined. The results have been used in the elucidation of the structure of an ecdysteroid, gerardiasterone, 93, 206 and in the preparation 207 of possible intermediates in the formation of bile acids from cholesterol.…”
Section: Cholestanesmentioning
confidence: 99%